2021
DOI: 10.1016/s2352-3026(20)30366-5
|View full text |Cite
|
Sign up to set email alerts
|

MATRix–RICE therapy and autologous haematopoietic stem-cell transplantation in diffuse large B-cell lymphoma with secondary CNS involvement (MARIETTA): an international, single-arm, phase 2 trial

Abstract: Summary Background Secondary CNS lymphoma is a rare but potentially lethal event in patients with diffuse large B-cell lymphoma. We aimed to assess the activity and safety of an intensive, CNS-directed chemoimmunotherapy consolidated by autologous haematopoietic stem-cell transplantation (HSCT) in patients with secondary CNS lymphoma. Methods This international, single-arm, phase 2 trial was done in 24 hospitals in Italy, the UK, the Netherlands, and Switze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
114
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(119 citation statements)
references
References 23 publications
5
114
0
Order By: Relevance
“…With the inclusion of ifosfamide, they addressed concerns about the efficacy of cyclophosphamide, utilized in their previous study, to cross the blood-brain barrier. Although 2-year overall survival with 46% was not improved in comparison to previous studies, Ferreri et al [13] demonstrated a better survival for patients with CNS involvement at first diagnosis, with 71% alive after 2 years and an improvement in the overall safety of the new protocol. In order to add real-world evidence to the advances described [10], we report the outcome of 17 patients treated according to the published treatment protocol at two academic centers in Germany.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…With the inclusion of ifosfamide, they addressed concerns about the efficacy of cyclophosphamide, utilized in their previous study, to cross the blood-brain barrier. Although 2-year overall survival with 46% was not improved in comparison to previous studies, Ferreri et al [13] demonstrated a better survival for patients with CNS involvement at first diagnosis, with 71% alive after 2 years and an improvement in the overall safety of the new protocol. In order to add real-world evidence to the advances described [10], we report the outcome of 17 patients treated according to the published treatment protocol at two academic centers in Germany.…”
Section: Introductionmentioning
confidence: 83%
“…More recently, the results of the multicenter phase 2 MARIETTA trial by Ferreri et al [13] were published. This trial investigates a similar regimen including chemoimmunotherapy based on MTX and ifosfamide followed by consolidation with high-dose chemotherapy and ASCT.…”
Section: Introductionmentioning
confidence: 99%
“…Another prospective trial called MARIETTA study was published recently and was supported to be the largest trial for secondary CNS lymphoma until now. 6 , 22 Treatment consisted of a sequential combination of two standardized chemotherapy regimens, MATRix (methotrexate, cytarabine, thiotepa, and rituximab) and RICE (rituximab, etoposide, ifosfamide, and carboplatin), followed by carmustine-thiotepa and autologous HSCT as a consolidation therapy. Seventy-nine patients were enrolled, and 2-year progression-free survival was 71% in patients with CNS disease at initial lymphoma diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Without any positive physical neurological examinations, a contrast-enhanced magnetic resonance imaging (MRI) scan of the brain suggested multiple enhancing masses in the corpus callosum and around the ventricles (Figure 1A-C). To make an accurate diagnosis, an 6 which was sponsored by International Extranodal Lymphoma Study Group (IELSG) and we decided to combine two standardized chemotherapy regimens, high dose methotrexate-based regimen (MT-R: methotrexate, temozolomide and rituximab) 7 for intracranial lesions and traditional R-CHOP (rituximab, vincristine, cyclophosphamide, prednisone and anthracycline) 8 immunochemotherapy regimen for extracranial lesions.…”
Section: Case Presentationmentioning
confidence: 99%
See 1 more Smart Citation